2020
DOI: 10.3390/cells9102304
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic and Tumor-Suppressive Functions of NOTCH Signaling in Glioma

Abstract: Although the role of NOTCH signaling has been extensively studied in health and disease, many questions still remain unresolved. Being crucial for tissue homeostasis, NOTCH signaling is also implicated in multiple cancers by either promoting or suppressing tumor development. In this review we illustrate the context-dependent role of NOTCH signaling during tumorigenesis with a particular focus on gliomas, the most frequent and aggressive brain tumors in adults. For a long time, NOTCH has been considered an onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 166 publications
(255 reference statements)
5
51
0
Order By: Relevance
“…NOTCH1 inhibitors have been tried in various preclinical studies, partially demonstrating effects on stem-like cells, although conflicting data exists and evidence for efficacy in clinical trials is still lacking 42 , 43 . Making use of the shRNA mediated knockdown of NOTCH1 we provide one possible explanation for those conflicting results: Although downregulation of NOTCH1 led to a depletion of the perivascular cell population, reduced tumor growth and reduced therapy resistance of cells in the PVN in line with previous reports 7 , 26 , 44 , 45 , it also induced TM- and network formation, thereby rendering the growth-deficient tumors virtually unsusceptible for the cytotoxic effects of radiotherapy. NOTCH1 proficiency is hence a key mechanism for the resilience of cells in the PVN, firstly by allowing population of that niche and secondly by being prerequisite for the protective properties of this specific microenvironment.…”
Section: Discussionsupporting
confidence: 71%
“…NOTCH1 inhibitors have been tried in various preclinical studies, partially demonstrating effects on stem-like cells, although conflicting data exists and evidence for efficacy in clinical trials is still lacking 42 , 43 . Making use of the shRNA mediated knockdown of NOTCH1 we provide one possible explanation for those conflicting results: Although downregulation of NOTCH1 led to a depletion of the perivascular cell population, reduced tumor growth and reduced therapy resistance of cells in the PVN in line with previous reports 7 , 26 , 44 , 45 , it also induced TM- and network formation, thereby rendering the growth-deficient tumors virtually unsusceptible for the cytotoxic effects of radiotherapy. NOTCH1 proficiency is hence a key mechanism for the resilience of cells in the PVN, firstly by allowing population of that niche and secondly by being prerequisite for the protective properties of this specific microenvironment.…”
Section: Discussionsupporting
confidence: 71%
“…Indeed, by manipulating this pathway through different approaches (constitutively-activated form, pharmacology and DLL4 ligand), we found that Notch1 activation globally reduced the expression of oligodendrocytic genes, while concomitantly increasing KCNN3 and APOE, which are typically associated with the astrocytic lineage. This was accompanied by reduction of proliferation in LGG275 cells as previously seen in high grade gliomas [27,59]. Using non-tumoural human O4-purified cells, we also found that activation of Notch1 reduced oligodendrocytic gene expression while upregulating CRYAB, KCNN3 and SOX9.…”
Section: Discussionsupporting
confidence: 83%
“…S14B). Collectively, these data fuel the emerging notion that Notch1 pathway acts as a tumor suppressor in DLGG [59].…”
Section: Discussionsupporting
confidence: 63%
“…In many other tumor types, oncogenic vs. tumor suppressor functions of Notch may strongly depend on the tissue of origin, the differentiation status, composition of the TME, invasion of immune cells or immune cell evasion, and the genetic background: It is clearly the context that matters most with Notch. For example, genetic GOF events of Notch receptors (amplification or point mutations) that promote Notch activity appear to support the initiation and progression of gliomas (neuronal differentiation, in [ 29 ]) and other non-epithelial cancers, such as osteosarcoma (mesenchymal differentiation; in [ 30 ]) or SCLCs (neuro-endocrine differentiation, in [ 31 ]); although the evidence is controversial: for example, recent articles report both oncogenic and tumor-suppressor functions for NOTCH in glioma [ 29 ]. However, also in some carcinomas, or tumors of epithelial origin, such as gastrointestinal (stomach, oesophagus) and colorectal cancers, GOF or oncogenic Notch mutations appear predominant.…”
Section: The Relevance Of Notch Mutations Amplification Pathwaysmentioning
confidence: 99%
“…The complex interactions between Notch and up- or downstream regulatory mechanisms often make it difficult to understand the true functional impact of NOTCH mutations and altered Notch signaling in the context of cancer cells and tissues. For example, in glioma, NOTCH can act as both tumor suppressor and oncogene (reviewed in detail in [ 29 ]). Oncogenic, activating Notch mutations recently identified in glioma may specifically promote and maintain the stem-cell characteristics of glioma cells, the most aggressive type of brain tumors in humans.…”
Section: The Relevance Of Notch Mutations Amplification Pathwaysmentioning
confidence: 99%